Comprehensive bioinformatics analysis of malignant transformation and potential therapeutic possibility of lung adenocarcinoma after lipopolysaccharide induction - Wanjie Xu; Wanjie Xu; Jing Zhang; Xinyu Zhang; Xue Wang; Yiluo Xie; Shengping Min; Shengping Min; Xiaojing Wang; Xiaojing Wang; Chaoqun Lian (Frontiers in Genetics)
BackgroundLipopolysaccharides are involved in malignant progression and epithelial-mesenchymal transition of cancer. The mechanism of LPS in malignant progression of lung adenocarcinoma and possible therapeutic strategies need to be explored.MethodsAfter obtaining LPS-induced characteristics, 850 samples were characterized. Differences in features were evaluated in different risk subgroups. Cell lines with high scoring performance were selected for in vitro experimental validation and possible potential therapeutic options were identified.ResultsBy using bioinformatics analysis to obtain LPS signature genes from the LPS induction cohort, the five intersecting genes were utilized to construct a risk model associated with LPS induction. The high-risk score subgroup had a poorer prognosis and lower immunotherapy response, and this subgroup showed distinct EMT features such as hypoxia pathway, high enrichment of WNT pathway and high TP53 mutation. After verifying that the risk model has a close correlation with EMT progression, we obtained cell lines with high EMT-associated features, confirming the possibility of LPS-induced EMT, i.e., demonstrating that LPS acts in inducing EMT progression. The malignant progression of tumors could be inhibited using rosiglitazone and liraglutide combined with lipid-forming trans-differentiation therapy.ConclusionIn the field of bioinformatics, our study acquired genes characteristic of lipopolysaccharide-induced lung adenocarcinomas and elucidated for the first time that LPS-induced associated scoring patterns correlate with EMT progression. In addition, we propose the possibility of treatment with trans-differentiation therapies that utilize the high plasticity that EMT progressing cancer cells have.